2019
DOI: 10.3390/nu11020356
|View full text |Cite
|
Sign up to set email alerts
|

Perilla frutescens Sprout Extract Protect Renal Mesangial Cell Dysfunction against High Glucose by Modulating AMPK and NADPH Oxidase Signaling

Abstract: Perilla frutescens (L.) Britt. var. japonica (Hassk.) Hara (PF), is a medical herb of the Lamiaceae family. We have previously reported that the PF sprout extract (PFSE) is effective in treating hyperglycemia. However, the role of PFSE on glomerular mesangial cells (MCs) proliferation and the extracellular matrix (ECM) accumulation in a diabetic condition are still unclear. Therefore, in this study, we have investigated the role of PFSE on cell proliferation and ECM accumulation in murine glomerular MCs (MMCs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Resveratrol treatment in db/db mice prevented NOX4 expression primarily due to increased AMPK activity [132]. Similarly, numerous recent studies highlighted the beneficial effects of antioxidants or other compounds against renal injuries implicating AMPK/NOX4/ROS [133][134][135][136][137][138][139]. Furthermore, two independent studies reported that Sestrin-2 mediated activation of AMPK inhibits ROS production, podocyte impairment in the hyperglycemic condition, and suppresses NOX4 in glomerular mesangial cells [140,141].…”
Section: Ampk and Oxidative Stressmentioning
confidence: 95%
“…Resveratrol treatment in db/db mice prevented NOX4 expression primarily due to increased AMPK activity [132]. Similarly, numerous recent studies highlighted the beneficial effects of antioxidants or other compounds against renal injuries implicating AMPK/NOX4/ROS [133][134][135][136][137][138][139]. Furthermore, two independent studies reported that Sestrin-2 mediated activation of AMPK inhibits ROS production, podocyte impairment in the hyperglycemic condition, and suppresses NOX4 in glomerular mesangial cells [140,141].…”
Section: Ampk and Oxidative Stressmentioning
confidence: 95%
“…Interestingly Perilla extracts also increased keratinocyte proliferation, which suggests that they might protect against keratinocyte aging. The antioxidant effects of Perilla leaf extracts have been previously studied in pharmacological properties [ 7 ]. Perilla leaf has been used as a traditional medicine to treat depression, anxiety, tumors, coughs, allergies, and other conditions, and our findings suggest that Perilla leaf and callus extracts could be used to treat keratinocyte damage and UV exposure-induced keratinocyte conditions [ 6 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Perilla frutescens (Perilla) is an annual herb widely cultured in Asia. Perilla leaves are known to have antioxidant, anti-inflammatory, and anti-allergic effects and to be rich in polyphenols [ 6 , 7 ]. Calluses (as known as plant stem cells) are disorganized, non-differentiated plant cell masses and are induced using hormones, such as auxin or cytokinin from plant explants [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…These findings show that HIF1α also contributed to the increase in NOX4 activity in this study. In this context, several studies have reported that NOX4 and AMPKα are inversely correlated in cardiac ventricular tissue, renal mesangial cells and podocytes [ 32 , 56 , 57 ]. Our work also shows that NOX4 hyperactivation leads to disturbances in AMPKα phosphorylation in adipocytes.…”
Section: Discussionmentioning
confidence: 99%